Improving Elderly Patients Medication Appropriateness in an Internal Medicine Ward: Application of the STOPP/START Criteria - Teles,Miguel Oliva (2020)
Introduction: In elderly people, polypharmacy and inappropriate prescribing are prevalent and associated with adverse events. STOPP/START criteria are a tool aiming to improve elderly medication appropriateness that has shown good validity, inter-rater reliability and applicability. Our aim was to evaluate the impact of the application of STOPP/START criteria version 2 to the prescription of hospitalized elderly patients. Methods: A prospective, single-centre study carried out in a tertiary internal medicine ward. Patients admitted with 65 years or more and with 5 or more medications were randomized to receive either usual physician and pharmacist care (control) or providing the patient´s attending medical team, within the first 72 hours, a pop-up recommendation indicating potentially inappropriate medications (PIM) and potentially prescribing omissions (PPO) as a result of the application of the STOPP/START version 2 criteria (intervention). Statistical analysis done with SPSS version 23 considered a p < 0.05. Results: 156 patients were included and randomized, and 64 on the intervention group and 62 on the control group were analysed. The team observed an average PIM and PPO reduction of 49% and 31% in the intervention group versus 13% and 0% in the control group (p = 0.01). There was an average acceptance of 63% for STOPP and 40% for START criteria recommendations. In the overall population the team found a prevalence of polypharmacy of 21% and of inappropriate prescription (at least one PIM) of 75.4% and identified a total of 230 PIM and 153 PPO. Conclusion: The team reports a high prevalence of polypharmacy and inappropriate prescription among Portuguese elderly patients admitted to an internal medicineward. The latter was significantly reduced using pop-up recommendations reporting the application of STOPP/START version 2 criteria within 72 hours of admission.